2013
DOI: 10.1248/cpb.c12-00468
|View full text |Cite
|
Sign up to set email alerts
|

Method to Increase the Systemically Delivered Amount of Drug from Dissolving Microneedles

Abstract: To increase the absorbed amount of a drug from dissolving microneedles (DMs), three DM array chips were prepared in which (1) the drug was localized at the acral portion of DMs, (2) the drug was loaded in each whole DM, and (3) the drug was loaded in DMs and the chip. Fluorescein free form (FL) and its sodium salt (FLNa) were used as model drugs. The DM array chip had 15-mm diameter with 225 DMs, each 500-µm long with a 300-µm diameter base. The respective FLNa contents in the three chips were (1) Key words s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…37 Integration of high loading efficiency backing layer to the microneedle shafts does not require any ancillary equipments as has been reported previously. 26 Fabrication of the whole integrated patch system can be achieved within 1-2 minutes, thus commercial scaling up and production of these 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 23 microneedles is feasible. With more than 1.5 billion people around the world suffering from chronic pain and the pain management market projected to grow to about USD$60 billion by 2015, this microneedle integrated transdermal patch can possibly serve as a viable source for the transdermal delivery of lidocaine with a faster rate of pain relief as compared to the commercially available patch and creams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Integration of high loading efficiency backing layer to the microneedle shafts does not require any ancillary equipments as has been reported previously. 26 Fabrication of the whole integrated patch system can be achieved within 1-2 minutes, thus commercial scaling up and production of these 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 23 microneedles is feasible. With more than 1.5 billion people around the world suffering from chronic pain and the pain management market projected to grow to about USD$60 billion by 2015, this microneedle integrated transdermal patch can possibly serve as a viable source for the transdermal delivery of lidocaine with a faster rate of pain relief as compared to the commercially available patch and creams.…”
Section: Discussionmentioning
confidence: 99%
“…25 Drug amounts in the range of 1-3 mg have been encapsulated at the maximum using polymeric microneedles. Ito et al recently demonstrated the attachment of drug loaded chip fabricated by pouring a drug-polymer glue in the molds of a tabletting machine, to a microneedle array fabricated by conventional mold based process to achieve a drug encapsulationof 12 mg. 26 5…”
Section: Introductionmentioning
confidence: 99%
“…In general, non-dissolvable microneedles are made of inorganic materials, such as metal, silicon, glass, and ceramics, while dissolvable microneedles are made from water-soluble biopolymers, such as sulfate dextran and chondroitin, in which the drugs are applied as a suspension that dissolves into the skin. 167 In fact, the eye may also be a target organ for microneedle application. 168 This technology can be applied to the delivery of DNA, viral capsid subunits, and inactivated and live attenuated vaccines.…”
Section: Transcutaneous Vaccinationmentioning
confidence: 99%
“…Compared to the SH-G group, the cumulative permeation quantity and rate of SH from the SH-DM were 3.36-and 3.32-fold at 48 h, respectively. The results indicated that the cumulative permeation quantity of SH was Dissolving microneedles enhanced its absorption 3 significantly enhanced in SH-DM formulation which successfully broke and penetrated through the stratum corneum 56,57 .…”
Section: Resultsmentioning
confidence: 99%